The Routledge Handbook of Literary Translingualism - Kellman, Steven G.; Lvovich, Natasha (Taylor & Francis, 2022)
Though it might seem as modern as Samuel Beckett, Joseph Conrad, and Vladimir Nabokov, translingual writing - texts by authors using more than one language or a language other than their primary one - has an ancient pedigree. The Routledge Handbook of Literary Translingualism aims to provide a comprehensive overview of translingual literature in a wide variety of languages throughout the world, from ancient to modern times. The volume includes sections on: translingual genres - with chapters on memoir, poetry, fiction, drama, and cinema ancient, medieval, and modern translingualism global perspectives - chapters overseeing European, African, and Asian languages. Combining chapters from lead specialists in the field, this volume will be of interest to scholars, graduate students, and advanced undergraduates interested in investigating the vibrant area of translingual literature. Attracting scholars from a variety of disciplines, this interdisciplinary and pioneering Handbook will advance current scholarship of the permutations of languages among authors throughout time.